Disability and Rights: A Look from Instruments that Guarantee Educational and Informational Accessibility in Paraguay. - Chamorro Cristaldo, María Felicia (2024)
Disability has evolved historically and has been addressed from a variety of approaches, and the social model underpins the Convention on the Rights of Persons with Disabilities. Another international instrument inspired by the Convention’s principles is the Marrakesh Treaty, which facilitates beneficiaries' access to reading and education. This article aims to examine these agreements approved by Paraguay, which are mechanisms for achieving an equitable and inclusive society. Also under consideration is the progress made in complying with the provisions of the Convention and the axes of the National Action Plan for the Rights of Persons with Disabilities. This public policy tool enables the cross-cutting of this issue in state institutions. A qualitative descriptive study methodology was employed through a bibliographic review of documentary research and technical reports within the scope of the current study's topic. While Paraguay has witnessed legislative progress recognizing the rights of this group, challenges persist in ensuring their effective implementation. Hence, it is crucial to have a coordinated effort between institutions and civil society organizations to achieve legislative initiatives and actions for educational and informational accessibility that consider the needs of this vulnerable social sector.